Urbanization and Carpobrotus edulis invasion alter the diversity and composition of soil bacterial communities in coastal areas - Novoa, Ana; Keet, Jan-Hendrik; Lechuga-Lago, Yaiza; Pyšek, Petr; Roux, Johannes J Le (FEMS microbiology ecology, 2020)
Coastal dunes are ecosystems of high conservation value that are strongly impacted by human disturbances and biological invasions in many parts of the world. Here, we assessed how urbanization and Carpobrotus edulis invasion affect soil bacterial communities on the north-western coast of Spain, by comparing the diversity, structure and composition of soil bacterial communities in invaded and uninvaded soils from urban and natural coastal dune areas. Our results suggest that coastal dune bacterial communities contain large numbers of rare taxa, mainly belonging to the phyla Actinobacteria and Proteobacteria. We found that the presence of the invasive C. edulis increased the diversity of soil bacteria and changed community composition, while urbanization only influenced bacterial community composition. Furthermore, the effects of invasion on community composition were conditional on urbanization. These results were contrary to predictions, as both C. edulis invasion and urbanization have been shown to affect soil abiotic conditions of the studied coastal dunes in a similar manner, and therefore were expected to have similar effects on soil bacterial communities. Our results suggest that other factors (e.g. pollution) might be influencing the impact of urbanization on soil bacterial communities, preventing an increase in the diversity of soil bacteria in urban areas.
Keywords: Soil Microbiology; Španělsko; ekosystém; zavlečené druhy; půdní mikrobiologie; Soil; Spain; urbanizace; Ecosystem; Bacteria; Introduced Species; půda; Urbanization